2018
DOI: 10.1038/s41467-018-05883-1
|View full text |Cite|
|
Sign up to set email alerts
|

Solar superstorm of AD 774 recorded subannually by Arctic tree rings

Abstract: Recently, a rapid increase in radiocarbon (14C) was observed in Japanese tree rings at AD 774/775. Various explanations for the anomaly have been offered, such as a supernova, a γ-ray burst, a cometary impact, or an exceptionally large Solar Particle Event (SPE). However, evidence of the origin and exact timing of the event remains incomplete. In particular, a key issue of latitudinal dependence of the 14C intensity has not been addressed yet. Here, we show that the event was most likely caused by the Sun and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 56 publications
2
55
0
Order By: Relevance
“…Since the phenomenon of rapid increase in CR intensity in 775 CE was solved 1-3 , 14 C analysis in annual rings has played a major role in searching for another rapid 14 C increase event 4,5 . While such events have been suggested to originate from an extreme SPE [6][7][8][9][10] , the other type with a rather long period of 14 C increase has recently been reported in German oak tree rings 11 . It is the 14 C increase in ca.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Since the phenomenon of rapid increase in CR intensity in 775 CE was solved 1-3 , 14 C analysis in annual rings has played a major role in searching for another rapid 14 C increase event 4,5 . While such events have been suggested to originate from an extreme SPE [6][7][8][9][10] , the other type with a rather long period of 14 C increase has recently been reported in German oak tree rings 11 . It is the 14 C increase in ca.…”
mentioning
confidence: 99%
“…galactic cosmic rays (GCRs) modulated by a variation in the interplanetary magnetic fields due to solar activities, gamma-rays from supernova (SN) and gamma-ray burst (GRB), and an extreme SPE. Recently, O'Hare et al showed sharp increases of 10 Be and 36 Cl concentrations with high-resolution in Greenland ice cores around 2610BP (~660 BC) 12 . We name the phenomenon the "~660 BCE event" including the 14 C increase at ca.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The 775 event was identified even in the decadal 14 C data (INTCAL) and 10 Be data (Dome Fuji [DF] ice core) as a rapid change (Usoskin & Kovaltsov, 2012). The 775 and 994 events were confirmed by subsequent independent annual 14 C measurements using worldwide tree samples (Büntgen et al, 2018;Fogtmann-Schulz et al, 2017;Güttler et al, 2015;Jull et al, 2014;Miyake et al, 2012Miyake et al, , 2013Miyake et al, , 2014Park et al, 2017;Rakowski et al, 2015;Usoskin et al, 2013;Uusitalo et al, 2018). Carbon-14 is a nuclide produced by cosmic rays (CR), which are high energy particles with origins in outside the solar system (Galactic CR: GCR) or an eruption of the sun (Solar Energetic Particles).…”
Section: Introductionmentioning
confidence: 82%